2012
DOI: 10.1007/s00603-012-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods for Determining Crack Initiation in Compression Tests on Low-Porosity Rocks

Abstract: Laboratory testing of rocks is traditionally carried out to determine the peak strength using the ISRM Suggested Methods or other suitable standards. However, it is well known that in low-porosity crystalline rocks there are at least three distinct stages of compressive loading that can be readily identified if the stress-strain response is monitored during the loading process: (1) crack initiation, (2) unstable crack growth, i.e., crack coalescence and (3) peak strength. Crack initiation is noted as the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(99 citation statements)
references
References 25 publications
2
86
0
2
Order By: Relevance
“…C is calculated by two methods, VS (Volumetric Strain) based on Brace et al (1966) and LSR (Lateral Strain Response) based on Nicksiar and Martin (2012). Crack damage stress, σ cd , indicates the stress of maximum volumetric strain.…”
Section: Bridgeman 1949mentioning
confidence: 99%
“…C is calculated by two methods, VS (Volumetric Strain) based on Brace et al (1966) and LSR (Lateral Strain Response) based on Nicksiar and Martin (2012). Crack damage stress, σ cd , indicates the stress of maximum volumetric strain.…”
Section: Bridgeman 1949mentioning
confidence: 99%
“…Other researchers suggest that crack initiation related to the Kaiser effect (will be discussed later) can be used to establish the in-situ state of stress (Seto et al 1999). Nicksiar and Martin (2012) proposed that the ISRM (International Society for Rock Mechanics) suggested methods be revised to include procedures suitable for establishing the crack-initiation stress.…”
Section: Introductionmentioning
confidence: 99%
“…The methods for detecting crack initiation have utilized either the volumetric strain or the lateral strain (Brace et al, 1966;Bieniawski, 1967b;Lajtai, 1974;Stacey, 1981), and have been modified by various researchers (Martin and Chandler, 1994;Diederichs, 2007, Nicksiar andMartin 2012). It has been shown that crack initiation is difficult to identify from the volumetric strain method, particularly if the specimen already contains a high density of cracks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations